Making Egg Hatching Machines Based on Simple Technology to Increase Poultry Production in Watumotobe Village, Kapontori District, Buton Regency: Pembuatan Mesin Tetas Telur Berbasis Teknologi Sederhana untuk Meningkatkan Produksi Unggas di Kelurahan Watumotobe, Kecamatan Kapontori Kabupaten Buton - Badaruddin, Rusli; Saili, Takdir; Hakim, Muh Haidir; Kimestri, Asma Bio; Putri, Anindyaningrum Zainal; Ilahude, Meygi Caesarika Putri (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2025)
Training on hatching machine manufacturing in Watumotobe Village, Kapontori Subdistrict, Buton District, aims to increase the capacity of local farmers in optimizing poultry egg hatching independently and efficiently. The majority of people in this area still use traditional methods that are less efficient in the hatching process, limiting poultry productivity. This training provides technical skills to farmers to build and operate simple hatching machines with optimal temperature and humidity settings. The application of this technology is expected to increase egg hatching rates, save time, and reduce dependence on the mother hen in the hatching process. In addition to improving technical skills, this training aims to empower the community economically and encourage self-reliance in poultry farming based on appropriate technology. The results of the training showed that participants gained a better understanding of the ideal hatching process and were able to modify the hatching machine according to local needs. This training can encourage the development of a more productive, sustainable poultry farming business and improve community welfare in Buton District.